Effect of phase difference in multi-antenna microwave thermal ablation for breast cancer treatment - Phasukkit, Pattarapong; Sanpanich, Arthorn; Tungjitkusolmun, Supan; Hamamoto, Kazuhiko (My University, 2013)
It was realized that cancer in breast is one of the most health hazards threatening women around the world for many years. Thermal ablation by using microwave energy is another alternative surgical maneuver due to its minimally invasive therapeutic technique. In this research, we investigate an effect of phase difference between three adjacent openedslot coaxial probes in a multiple antenna alignment of microwave thermal ablation system for breast cancer treatment. FEM by using COMSOL is an implementation tools to simulate for 0, 45, 90, 135 and 180 degree of phase difference. 3D Simulation results show that temperature distribution pattern, destructive volume and SAR in breast tissue are affected from those phase-shift utilization in multi-antenna system significantly. © 2013 IEEE.